Marx and Wittgenstein : knowledge, morality and politics - Kitching, G. N.; Pleasants, Nigel, 1962- (Routledge studies in social and political thought ;, 2002)
This book develops and extends the unorthodox view that there are deeper philosophical commonalities between Marx and Wittgenstein than may at first be apparent.